SPECIFICITY OF APPLICATION OF MARKETING IN SPORTS (Heritage, 2023)
Marketing in sports is an area that, in addition to promotion as the most transparent set of activities in this area, also includes research, segmentation, positioning, then decisions about the product, price, distribution, employees, etc. The extent to which authors from this field have all the mentioned marketing potentials in their considerations depends primarily on understanding the breadth of the sports industry. This paper takes the position that the sports industry includes athletes and sports events, as well as the material sports industry, that is, manufacturers of equipment, clothing, and footwear, as well as providers of sports services. Another inaccuracy in defining the potential of marketing stems from the fact that the sports industry, expressed in this way, brings certain circumstances that produce peculiarities in the application of marketing in sports. In addition, a rapidly growing market such as sports, which is simultaneously stimulated by the rapid growth of information and communication technologies, i.e. social media, modifies existing marketing tools and processes, but also creates some new ones. The aim of the paper is to define the peculiarities in the application of marketing tools and processes in the sports industry. The scientific contribution is based on the views of different authors from the field of marketing in sports and related fields, as well as on the issue of the choice and application of marketing tools and processes. The analysis of available literature, i.e. secondary data sources, confirmed the basic research hypothesis that the application of marketing tools and processes implies certain specificities in relation to their application in other areas.
Keywords: Marketing, sport, public relations, sponsorship, athletes, sports events.